Changes in eating behaviours following bariatric surgery: A prospective study - Subramaniam, Kavitha (2021)
Adopting healthy eating behavior is important in achieving successful weight loss after bariatric surgery. This study aims to determine the changes in eating behaviors 6 months after surgery. Fifty-seven patients who went through bariatric surgery in two tertiary referral hospitals were recruited and interviewed before surgery (T0), three (T1), and six (T2) months after surgery. Eating behaviors were assessed using the Dutch Eating Behavior Questionnaire (DEBQ), which measured emotional, external, and restrained eating. Higher subscale scores indicate strong behavioral traits. Other information including psychological distress, quality of life, socio-demography, and morbidity were collected. Generalized Estimating Equation (GEE) model was developed to study the change in eating behaviors and its’ predictors over time. Participants of the study were mostly women, from the Malay ethnic group and the average age at the time of surgery was 39.4 years. Emotional and external eating scores changed significantly over time with the values recorded at various time intervals as follows: 2.06 and 2.86 before surgery; 1.64 and 2.25 three months after surgery; and 1.81 and 2.40, 6 months after surgery. Reduction in the third month followed by a slight increase at the sixth was noted. Restrained eating did not show a significant change. The presence of diabetes was also associated with higher emotional and external eating scores. Further, higher anxiety scores were associated with higher external eating. Favorable changes in eating behaviors were noted after bariatric surgery. However, a risk of a reversal in the improvement was present. The emotional and external eating behaviors in surgical candidates should be identified and addressed accordingly with special attention to diabetic patients. © 2021, Editorial board of Journal of Experimental Biology and Agricultural Sciences. All rights reserved.